A mathematical model to optimize transport cost and inventory level in a single level logistic network - Laila Kechmane; Benayad Nsiri; Azeddine Baalal (Computational Problems in Science and Engineering, 2015)
This paper proposes a mathematical model that minimizes transportation costs and optimizes distribution organization in a single level logistic network. The objective is to allocate customers to distribution centers and vehicles to travels in order to cut down the traveled distances, while observing the storage capacities of vehicles and distribution centers and covering the customers’ needs. We propose a mixed integer programming formula that can be solved using Lingo 14.0. A digital example will be given in the end to illustrate the practicability of the model.
Keywords: Distribution organization; Mixed integer programming; Single level logistic network; Transportation costs